(untitled) (Bangladesh Journal of Botany, 2021)
Rapid Visco Analyzer (RVA) profiles are important traits for indicating rice quality, which are controlled by quantitative trait loci (QTL). In the past two decades, hundreds of QTL for rice RVA profiles have been detected, but without an integration study. Consistent QTL regions associated with rice RVA profiles by QTL meta-analysis with genetic information of 592 QTL for eight RVA profiles were studied. A total of 82 meta-QTL for RVA profiles were detected on 12 chromosomes. MQTL possessed narrower confidence intervals than the initial QTL and candidate genes were identified within each MQTL. These MQTL and candidate genes are beneficial for future marker-assisted selection gene cloning. Bangladesh J. Bot. 50(2): 269-276, 2021 (June)